FDEM Modelling of Rock Fracture Process during Three-Point Bending Test under Quasistatic and Dynamic Loading Conditions. (5th August 2021) - An, Huaming; Song, Yushan; Liu, Hongyuan
Abstract : A hybrid finite-discrete element method (FDEM) is proposed to model rock fracture initiation and propagation during a three-point bending test under quasistatic and dynamic loading conditions. Three fracture models have been implemented in the FDEM to model the transition from continuum to discontinuum through fracture and fragmentation. The loading rate effect on rock behaviour has been taken into account by the implementation of the relationship between the static and dynamic rock strengths derived from dynamic rock fracture experiments. The Brazilian tensile strength test has been modelled to calibrate the FDEM. The FDEM can well model the stress and fracture propagation and well show the stress distribution along the vertical diameter of the disc during the Brazilian tensile strength test. Then, FDEM is implemented to study the rock fracture process during three-point bending tests under quasistatic and dynamic loading conditions. The FDEM has well modelled the stress and fracture propagation and can obtain reasonable fracture toughness. After that, the effects of the loading rate on the rock strength and rock fracture toughness are discussed, and the mesh size and mesh orientation on the fracture patterns are also discussed. It is concluded that the FDEM can well model the rock fracture process by the implementation of the three fracture models. The FDEM can capture the loading rate effect on rock strength and rock fracture toughness. The FDEM is a valuable tool for studying the rock behaviour on the dynamic loading although the proposed method is sensitive to the mesh size and mesh orientation.